2017
DOI: 10.1186/s12936-017-1680-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline in the susceptibility of Plasmodium falciparum to dihydroartemisinin–piperaquine in the south of Vietnam

Abstract: BackgroundArtemisinin resistant Plasmodium falciparum has emerged in the countries of the Greater Mekong sub-region posing a serious threat to global malaria elimination efforts. The relationship of artemisinin resistance to treatment failure has been unclear.MethodsIn annual studies conducted in three malaria endemic provinces in the south of Vietnam (Binh Phuoc, Ninh Thuan and Gia Lai) between 2011 and 2015, 489 patients with uncomplicated P. falciparum malaria were enrolled in detailed clinical, parasitolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 19 publications
3
149
2
1
Order By: Relevance
“…falciparum malaria among the total number of cases of malaria in those regions. The clinical impact of this genetic change has been high: the appropriate clinical and parasitological response (APCR) rates for DP treatment were 93% and 86% in 2010 (13) and 2014, respectively, but the rate dropped to 78% in 2015 (14). The results of the present study confirm the spread of the phenotype with a long clearance half-life as well as an increase in the frequency of various K13 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…falciparum malaria among the total number of cases of malaria in those regions. The clinical impact of this genetic change has been high: the appropriate clinical and parasitological response (APCR) rates for DP treatment were 93% and 86% in 2010 (13) and 2014, respectively, but the rate dropped to 78% in 2015 (14). The results of the present study confirm the spread of the phenotype with a long clearance half-life as well as an increase in the frequency of various K13 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, parasite persistence and slow clearance in African studies are not associated with the pfk13 polymorphism [10,21]. Secondly, K13 variants do not determine parasite recurrence after treatment with the ACT DHA-piperaquine (DP), as recently reported for three sites in Vietnam [17]. The Gia Lai site, in which 67% of P. falciparum malaria patients carried the C580Y variant of pfk13, showed 89% treatment success ('adequate clinical and parasitological response', ACPR), whereas the ACPR among patients enrolled at Ninh Thuan was 78% (C580Y prevalence rate 4%), and among patients enrolled at Binh Phuoc, the ACPR was a very disappointing 56% (C580Y prevalence rate 73%).…”
Section: The Perceived Threat To Artemisinin-based Malaria Therapeuticsmentioning
confidence: 58%
“…The Gia Lai site, in which 67% of P. falciparum malaria patients carried the C580Y variant of pfk13, showed 89% treatment success ('adequate clinical and parasitological response', ACPR), whereas the ACPR among patients enrolled at Ninh Thuan was 78% (C580Y prevalence rate 4%), and among patients enrolled at Binh Phuoc, the ACPR was a very disappointing 56% (C580Y prevalence rate 73%). In fact, the best interpretation of this study is that it is falling partner drug efficacy that has led to the low ACPR in some sites [17]. Furthermore, in Myanmar, despite a prevalence rate of 25-65% of the C580Y variant pfk13 in 2012 and 2013 in Kawthaung and Myawaddy, 3 days of standard ACT delivered ≥96% ACPR [22].…”
Section: The Perceived Threat To Artemisinin-based Malaria Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dihydroartemisinin (DHA) is a semisynthetic derivative of artemisinin (ARS) isolated from the traditional Chinese herb Artemisia annua L.; it has been frequently used in the treatment of malaria (1,2). Previous studies have reported that DHA also has potent antitumor effects; however, its anticancer mechanism is not well understood (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%